Product Catalog Creation as Visual Identity for Woro Srikandi Batik Pacitan - Achmad, Zainal Abidin; Arifianto, Pungky Febi (STMIK Royal, 2025)
Abstract: Batik Woro Srikandi, a traditional batik producer in Arjowinangun, Pacitan, faces significant challenges in digital marketing. This issue stems from a lack of professional promotional media and an underdeveloped visual identity, hindering the product's ability to compete in an increasingly competitive market. To address these constraints, the community service team designed an initiative comprising several methodological stages: (1) conducting a needs analysis of the partner through observation and interviews; (2) implementing training sessions on product photography and design; and (3) facilitating participatory mentorship for the local artisans in catalog production and visual identity development. The primary outcome of this project was the successful creation of a professional product catalog that features a consistent brand visual identity. This catalog is designed to strengthen brand identity, expand market reach, and provide a competitive advantage for Batik Woro Srikandi. It is anticipated that this catalog will not only enhance customer engagement and sales but also contribute to the long-term sustainability of Pacitan's traditional batik art. Keywords: traditional batik; visual identity; product catalog; woro srikandi batik; digital branding Abstrak: Batik Woro Srikandi sebagai produsen batik tradisional di Arjowinangun, Pacitan, menghadapi kendala dalam pemasaran digital karena kurangnya media promosi yang profesional dan identitas visual yang kuat, sehingga menyulitkan produknya bersaing di pasar yang semakin kompetitif. Untuk mengatasi hal ini, kegiatan pengabdian masyarakat ini dirancang dengan tahapan metode yang terdiri dari: (1) Analisis kebutuhan mitra melalui observasi dan wawancara; (2) Pelaksanaan pelatihan fotografi produk dan desain; serta (3) Pendampingan dalam pembuatan katalog dan pengembangan identitas visual yang dilakukan secara partisipatif bersama perajin. Capaian utama dari kegiatan ini adalah terwujudnya sebuah katalog produk profesional yang memuat identitas visual merek yang konsisten. Tujuannya adalah untuk memperkuat brand identity, memperluas jangkauan pasar, dan memberikan keunggulan kompetitif bagi Batik Woro Srikandi. Diharapkan, katalog ini tidak hanya meningkatkan keterlibatan pelanggan dan penjualan, tetapi juga mendukung keberlanjutan seni batik tradisional Pacitan dalam jangka panjang. Kata kunci: batik tradisional; identitas visual; katalog produk; batik woro srikandi; branding digital